Clinical markers associated with acute laboratory-confirmed Dengue infection: results of a national epidemiological surveillance system (2017)
ABSTRACTObjective To evaluate the association of several clinical markers with acute laboratory-positive Dengue Virus infection.Methods A hospital-based case-control study was conducted in the state of Colima, Mexico, by using information from the National System of Epidemiological Surveillance (Sistema Nacional de Vigilancia Epidemiológica [SINAVE]) for Dengue. Data from 2 732 cases and 2 775 frequency-matched controls were analyzed. Odds Ratio (OR) and the 95 % Confidence Interval (CI), estimated by means of logistic regression models, were used.Results The presence of skin rash (OR=1,7; 95 % CI 1,5–2,1), persisting vomiting (OR=1,8; 95 % CI 1,5–2,3) and increased capillary fragility (petechiae, ecchymosis, hematoma or positive tourniquet test; OR=1,8; 95 % CI 1,2–2,6) were associated with laboratory-positive infection.Conclusions Three clinical markers were significantly associated with an increased risk of acute laboratory-confirmed dengue infection. These findings would support accurate and timely diagnosis of dengue in laboratory-limited settings.